Supraharmonic emission from a three-phase PV system connected to the LV grid. (November 2021) - Menti, Anthoula; Barkas, Dimitrios; Kaminaris, Stavros; Psomopoulos, Constantinos S.
Abstract: Existing international standards address harmonic orders up to the 40th or 50th (at 2 or 2.5 kHz for a 50 Hz network). Modern converters effectively suppress components within that range, but they also tend to shift emission to higher frequencies. Recently reported cases of disturbances in modern distribution grids specifically attributed to supraharmonics (harmonic components within the 2–150​ kHz range) have drawn interest in associated research. Grid-connected PV systems utilizing PWM-controlled inverters inject supraharmonic currents into the distribution network at their point of connection. Comprehension of their electrical behavior, including their impact on grid supraharmonic levels, can be achieved through extensive simulation studies. In this paper, a three-phase PV system is simulated using models successfully already developed for single phase PV inverters that increase simulation speed by avoiding time-consuming procedures. Current and voltage waveforms as well as supraharmonic levels are presented. The simulation results are compared with real measurements obtained from an operating small rooftop PV system and evaluated. Additional simulations are carried out using different values for system parameters and their respective impact on supraharmonic levels is assessed. Moreover, this paper presents real supraharmonics' measurements from a grid-connected 8kWp PV system.